Effects of Physical Training and Fitness on Running Injuries in Physically Active Young Men. Issue 1 (January 2017) - Grier, Tyson L.; Canham-Chervak, Michelle; Anderson, Morgan K.; Bushman, Timothy T.; Jones, Bruce H.
Abstract : Abstract: Grier, TL, Canham-Chervak, M, Anderson, MK, Bushman, TT, and Jones, BH. Effects of physical training and fitness on running injuries in physically active young men. J Strength Cond Res 31(1): 207–216, 2017—The purpose of this investigation was to determine the effects of physical training (PT) and fitness on risks for running-related injuries (RRIs) in physically active young men. Personal characteristics, PT, Army Physical Fitness Test scores, and injury data were obtained by survey. Army Physical Fitness Test variables (push-ups, sit-ups, and 2-mile run) were converted into quartiles (Q), where Q1 = lowest performance and Q4 = highest performance. Odds ratios (OR) and 95% confidence intervals (95% CI) were calculated using multivariate logistic regression. Over 4, 000 ( n = 4, 236) soldiers were surveyed. Running injury incidence was 14%. A greater risk of an RRI was associated with older age (OR31+/<22 years = 1.62, 95% CI, 1.21–2.18), higher BMI ( ), and total distance ran per week during unit PT (OR16.1+/1–5 miles = 1.66, 95% CI, 1.15–2.41). A lower risk of an RRI was associated with total distance run per week during personal PT (OR5.1–10/1–5 miles = 0.70, 95% CI, 0.53–0.91, OR10.1–16 +/1–5 miles = 0.58, 95% CI, 0.35–0.97, OR16.1+/1–5 miles = 0.54, 95% CI, 0.30–0.98), higher aerobic endurance as measured by 2-mile run performance (ORQ4/Q1 = 0.50, 95% CI, 0.35–0.72), and unit resistance training ≥3 times a week (OR≥3 times per week/none = 0.46, 95% CI, 0.29–0.73). Greater personal PT running mileage decreased injuries in this population suggesting that the increased protective effect of higher aerobic fitness outweighed the injurious effect of running more miles during personal PT. Countermeasures to prevent RRIs could entail enhancing aerobic endurance, providing opportunities for personal aerobic training, monitoring for excessive unit PT running mileage and encouraging unit resistance training ≥3 times per week.